Differential Proteomic Analysis of Listeria monocytogenes during High-Pressure Processing - Yi-An Chen; Guan-Wen Chen; Hao-Hsiang Ku; Tsui-Chin Huang; Hsin-Yi Chang; Cheng-I Wei; Yung-Hsiang Tsai; Tai-Yuan Chen (Biology, 2022)
High-pressure processing (HPP) is a prevailing non-thermal food preservation technology. The inactivation mechanisms of Listeria monocytogenes under HPP at 200 and 400 MPa for 3 min were investigated by label-free quantitative proteomic analysis and functional enrichment analysis in the Kyoto Encyclopedia of Genes and Genomes. HPP treatment at 400 MPa exhibited significant effects on proteins involved in translation, carbon, carbohydrate, lipid and energy metabolism, and peptidoglycan biosynthesis. HPP increased most ribosomal subunits and initiation factors, suggesting it might shift ribosomal biogenesis to translation initiation. However, protein synthesis was impaired by the shortage of proteins responsible for elongation, termination and recycling. HPP stimulated several ATP-dependent Clp proteases, and the global transcriptional regulator Spx, associating with activation of the stress-activated sigma factor Sigma B (σB) and the transcriptional activator positive regulatory factor A (PrfA) regulons. The quantitative proteomics approaches provide fundamental information on L. monocytogenes under different HPP pressures, and provide theoretical support for HPP against Listeriosis illness and for promotion of safer ready-to-eat foods.